2012
DOI: 10.1371/journal.pone.0038191
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Interaction and Membrane Perturbation of Human Islet Amyloid Polypeptide Monomer and Dimer by Molecular Dynamics Simulations

Abstract: The aggregation of human islet amyloid polypeptide (hIAPP or amylin) is associated with the pathogenesis of type 2 diabetes mellitus. Increasing evidence suggests that the interaction of hIAPP with β-cell membranes plays a crucial role in cytotoxicity. However, the hIAPP-lipid interaction and subsequent membrane perturbation is not well understood at atomic level. In this study, as a first step to gain insight into the mechanism of hIAPP-induced cytotoxicity, we have investigated the detailed interactions of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 55 publications
(89 reference statements)
4
53
0
Order By: Relevance
“…Zhang et al used an SDS-bound NMR structure of monomeric hIAPP to investigate the dynamics of hIAPP monomers and dimers with the N-terminus pre-inserted into 1-palmitoyl-2-oleoyl- sn -glycero-3-phosphoglycerol (POPG) bilayers using MD simulations. 41 They reported that the electrostatic interactions between the positively charged residues and negatively charged lipids are important for the peptide-membrane association. Furthermore, they also found that the C-terminal residues mostly mediate the inter-peptide interactions in the dimer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al used an SDS-bound NMR structure of monomeric hIAPP to investigate the dynamics of hIAPP monomers and dimers with the N-terminus pre-inserted into 1-palmitoyl-2-oleoyl- sn -glycero-3-phosphoglycerol (POPG) bilayers using MD simulations. 41 They reported that the electrostatic interactions between the positively charged residues and negatively charged lipids are important for the peptide-membrane association. Furthermore, they also found that the C-terminal residues mostly mediate the inter-peptide interactions in the dimer.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they also found that the C-terminal residues mostly mediate the inter-peptide interactions in the dimer. 41 It is, however, not known if and to what extent the peptide is inserted into the membrane, and the assumption that the N-terminal part of the peptide is the membrane-inserting element will of course influence the resulting model. Zhao et al have constructed membrane pores from ss-NMR structures of the hIAPP fibril 21 to determine the number of monomers per pore by comparing the size of the pores with AFM images.…”
Section: Introductionmentioning
confidence: 99%
“…Despite some remaining disputes and controversies, three most common mechanisms have been proposed: (i) the partially ordered oligomers directly penetrate and disrupt the structure of membrane which induces cell death; 20 (ii) the partially ordered oligomers can form ions or small-molecule membrane channels altering ion concentration balances between extracellular and intracellular environments, causing premature cell apoptosis; [21][22][23][24][25] (iii) the growth of rigid amyloid fibrils on a flexible membrane results in a change in the membrane curvature, largely disrupting the membrane structure and causing membrane breaches. 10,17,19,26,27 It is noteworthy that an essential prerequisite for the appearance a) J. Liu and Z. Yang contributed equally to this work. b) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…NFGAILS peptide is the core fibrillization segment of human islet amyloid polypeptide (hIAPP [22][23][24][25][26][27][28], and is directly involved in type II diabetes mellitus. 5,6 Many experiments and simulations have demonstrated the similarities between the NFGAILS aggregation cytotoxicity in pancreatic β-islet cell with respect to its full length peptide.…”
Section: Introductionmentioning
confidence: 99%
“…MD simulation has been used to investigate the orientation of membrane-bound antimicrobial peptides (MB21 [244], indolicidin [245], BLT2 [246], CM15 [247], piscidin-1 [248], δ-lysin [249]), an antibacterial peptide (bovine LFampin [55]), neuropeptides (neuropeptides B and W [250]), human immunodeficiency virus fusion peptides (T-1249 [251], FP-16 and -23 [252], and VP1 [253]), and transmembrane peptides (gramicidin A [254], M2 [255], carnobacteriocin B2 [256], TM2 [257], human islet amyloid polypeptide [258], human serum paraoxonase 1 [259], and gaduscidin-1 and -2 [260]) in zwitterionic or anionic membrane lipid bilayers. The membrane-bound peptides were inserted into the membrane perpendicular to the membrane surface, with the C-or N-terminus toward the inside of the membrane.…”
Section: Simulation Of Membrane-bound Peptidesmentioning
confidence: 99%